A SINFONI view of the nuclear activity and circumnuclear star formation in NGC 4303 – II. Spatially resolved stellar populations. Issue 4 (6th November 2018) - Dametto, Natacha Z; Riffel, R; Colina, L; Riffel, R A; Piqueras López, J; Davies, R I; Burtscher, L; Menezes, R B; Arribas, S; Pastoriza, M G; Labiano, A; Storchi-Bergmann, T; et al.
ABSTRACT: We present a spatially resolved stellar population study of the inner ∼200 pc radius of NGC 4303 based on near-infrared integral field spectroscopy with SINFONI/VLT at a spatial resolution of 40–80 pc and using thestarlight code. We found that the distribution of the stellar populations presents a spatial variation, suggesting an age stratification. Three main structures stand out. Two nuclear blobs, one composed by young stars ( t ≤ 50 Myr) and one with intermediate-age stars (50 Myr < t ≤ 2 Gyr), both shifted from the centre. The third one is an internal intermediate-age spiral arm-like structure, surrounding the blob of young stars. Our results indicate that star formation has occurred through multiple bursts in this source. Furthermore, the youngest stellar populations ( t ≲ 2 Gyr) are distributed along a circumnuclear star-forming ring with r ∼ 250 pc. The ring displays star formation rates (SFRs) in the range of 0.002–0.14 M⊙ yr −1, favouring the 'pearls-on-a-string' scenario. The old underlying bulge stellar population component ( t > 2 Gyr) is distributed outside the two blob structures. For the nuclear region (inner ∼60 pc radius) we derived an SFR of 0.43 M⊙  yr −1 and found no signatures of non-thermal featureless continuum and hot dust emission, supporting the scenario in which an LLAGN/LINER-like source is hidden in the centre of NGC 4303. Thus, our results reveal a rather complex star formation history in NGC 4303, with different stellar population components coexisting with a low efficiency accreting black hole in its centre.